A Case Report of Continuous Subcutaneous Infusion of Hydromorphone, Metoclopramide and Ondansetron Used to Treat Refractory Pain and Nausea in an Ambulatory Palliative Clinic - Lawrence Aoun; Josie Zakaria (Palliative Medicine and Hospice Care, 2017)
Background: This case report describes a patient with advanced breast cancer with both refractory pain related to metastatic skeletal lesions and nausea who was successfully managed during the last nine months of her life with a continuous subcutaneous infusion of hydromorphone, metoclopramide and ondansetron in one chemically compatible mixture. Case presentation: A 56-year-old woman with widespread metastatic breast cancer to bone who was followed in an ambulatory palliative care clinic for pain management and nausea. As her disease progressed and she was in the last year of her life, her pain and nausea had become very difficult to manage despite multiple modalities of treatment. Case management: A continuous subcutaneous infusion of hydromorphone, metoclopramide and ondansetron was started and titrated to achieve relief of her intolerable and refractory pain and nausea. All three medications were chemically compatible, and provision for bolus was ensured. Case outcome: The patients ultimate goals of care were achieved, including nine months of excellent relief of both nausea and pain, while enhancing quality of life due to ease of administration of one mixture. Conclusion: The combination of hydromorphone, metoclopramide and ondansetron is a potentially useful regimen for the targeted treatment of concomitant refractory pain and nausea in the palliative care setting. This represents the first time the triad mixture has been reported successfully in case studies.